THE DEVELOPMENT OF INDONESIAN TEACHING MEDIA FOR CHILDREN WITH SPECIAL NEEDS - Mastuti, Dewi Leni; Syahadati, Elly (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2020)
The use of learning media is a means of communication between teaching staff and students. Learning styles are no longer teacher-centered, but learning styles involve various aspects. These aspects are channeled through learning media. Teachers are no longer a source of learning but teachers must be able to create learning media. This research and development aims to describe the development of the Indonesian language and to describe the feasibility and quality of Indonesian language media. This development uses seven research steps, including (1) research and data collection, (2) planning, (3) initial product development, (4) initial testing, (5) design revision, (6) field trials, and ( 7) product revisions and improvements. The research instruments used were interviews and questionnaires. The results of the needs analysis reveal that the subject needs real media with attractive colors. Other findings indicate that Indonesian language learning media products are suitable for use in children with special needs. So it can be concluded that the Indonesian language learning media for deaf students in one of the schools with special needs in Pontianak is suitable for use as a learning medium in schools.Keywords: instructional media, interactive learning, Indonesian